2021
DOI: 10.3390/rs14010099
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Contributions of Climate Change and Human Activities to Water Volume in Lake Qinghai, China

Abstract: Lake Qinghai has shrunk and then expanded over the past few decades. Quantifying the contributions of climate change and human activities to lake variation is important for water resource management and adaptation to climate change. In this study, we calculated the water volume change of Lake Qinghai, analyzed the climate and land use changes in Lake Qinghai catchment, and distinguished the contributions of climate change and local human activities to water volume change. The results showed that lake water vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…The shifting of climate temperature and weather are caused by human activities [56]. This latter comes to play an adverse effect on livestock production through drought and heat [57].…”
Section: Climate Changementioning
confidence: 99%
“…The shifting of climate temperature and weather are caused by human activities [56]. This latter comes to play an adverse effect on livestock production through drought and heat [57].…”
Section: Climate Changementioning
confidence: 99%
“…The average elevation is approximately 3200 m. The length is approximately 109 km from east to west and the width is approximately 39.8 km from north to south. The climate in QHL is becoming warmer and more pluvial, and the lake water volume decreased by 9.48 km 3 from 1975 to 2004 and increased by 15.18 km 3 from 2005 to 2020 [7].…”
Section: Study Areamentioning
confidence: 99%
“…From the 1960s to the beginning of the 21st century, the water level of QHL continued to drop by 3 m and then rose sharply [6]. The contribution of climate change to lake water volume change was 97.55%, while the local human activities contribution was only 2.45% [7]. Thus, climate change has a dominant influence on water volume change in QHL.…”
Section: Introductionmentioning
confidence: 96%
“…Mu et al found that warming accelerated the decomposition of carbon after permafrost collapse, and transformed ecosystems from carbon sinks (1.75 μmol C·m −2 ·s −1 ) to weak carbon sources (0.05 μmol C·m −2 ·s −1 ) during the growing season on the northern QTP [ 16 ]. The Qinghai Lake Basin (QLB) located in the northeast of QTP, and is one of the most sensitive areas of global climate change [ 17 ]. As the primary vegetation type of QTP, the alpine meadow adapts to the long-term low temperature environment, and is highly sensitive to the environment change [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%